2017
DOI: 10.1371/journal.pone.0169998
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of Laribacter hongkongensis Reveals Adaptive Response Coupled with Temperature

Abstract: Bacterial adaptation to different hosts requires transcriptomic alteration in response to the environmental conditions. Laribacter hongkongensis is a gram-negative, facultative anaerobic, urease-positive bacillus caused infections in liver cirrhosis patients and community-acquired gastroenteritis. It was also found in intestine from commonly consumed freshwater fishes and drinking water reservoirs. Since L. hongkongensis could survive as either fish or human pathogens, their survival mechanisms in two differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 71 publications
2
1
0
Order By: Relevance
“…Consistently, the expression levels of crp was markedly increased under anaerobic conditions (Figure 6E) and acidic pHs (Figure 6F). Furthermore, we assessed the mRNA level of crp under growth temperatures of 20 and 37°C and did not observe any significant differences in growth rate (data not shown), which is in line with our previous transcriptomic data (Kong et al, 2017). These findings emphasize the important contributions of the transcription factor CRP for the biological fitness of L. hongkongensis .…”
Section: Resultssupporting
confidence: 89%
“…Consistently, the expression levels of crp was markedly increased under anaerobic conditions (Figure 6E) and acidic pHs (Figure 6F). Furthermore, we assessed the mRNA level of crp under growth temperatures of 20 and 37°C and did not observe any significant differences in growth rate (data not shown), which is in line with our previous transcriptomic data (Kong et al, 2017). These findings emphasize the important contributions of the transcription factor CRP for the biological fitness of L. hongkongensis .…”
Section: Resultssupporting
confidence: 89%
“…Recent transcriptomic studies have revealed the connection between temperature and virulence in marine pathogenic bacteria (Williams et al, 2014;Kong et al, 2017;Huang et al, 2018). In the current work, we demonstrate that Pdd undergoes a stress response at 37 • C, with heat-shock proteins accounting for the most upregulated functions at this temperature.…”
Section: Discussionsupporting
confidence: 57%
“…The serological detection methods were established ( Tse et al, 2014 ; Wang et al, 2017 ). The adaptive response and transcriptional regulation patterns of L. hongkongensis coupled with different nutritional sources, aerobic or anaerobic conditions, and different temperatures were also studied ( Xiong L. et al, 2015 ; Kong et al, 2016 , 2017 ; Xiong et al, 2017 , 2019 ). Researchers also discussed the pathogenicity factors of L. hongkongensis ( Xie et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%